Contact lens case cleaning procedures affect storage solution pH and osmolality - Abengózar-Vela, Antonio (2011)
Purpose. To investigate pH and osmolality changes in the solutions stored in contact lens (CL) cases, when different case rinsing and drying methods are used on a daily basis. Methods. Four multipurpose solutions (Opti-Free Express, Solo-Care Aqua, Re-Nu Multiplus, and Complete) and two hydrogen peroxide systems (AOsept and Oxysept) were studied. Cases were filled with the solutions and kept sealed. After 8 h, the cases underwent different rinsing (rinsing; non-rinsing) and drying (air drying-AD; lint-free tissue drying-LFTD; non-drying-ND) procedures on a daily basis. Five cases of each rinsing/drying combination for each solution were evaluated. The pH and osmolality of the case-contained solution were evaluated on the 1st, 7th, 15th, and then, 30th day. Results. pH and osmolality increased significantly from day 1 to 30, except for Complete in which a significant decrease in pH was found. Rinsing vs. non-rinsing CL cases did not have any influence on the pH or osmolality, except for Oxysept, which showed a significantly higher osmolality value when cases were not rinsed. However, the drying procedure did influence both measurements; pH was significantly higher in the AD compared with the ND group (p 0.05), and there was a significant difference in osmolality between the three drying conditions (p 0.05), with the AD group showing the highest values, and the LFTD group showing the lowest. Conclusions. Osmolality and pH values are time and drying process-dependent in a CL case cleaning schedule. Regarding drying conditions, LFTD causes less increase in osmolality. Future studies should determine whether these changes might affect bacterial growth, lens parameters, or subject comfort during CL wear.